Blood loss and transcapillary refill in uncontrolled treated hemorrhage in dogs (Clinics, 2010)
OBJETIVE: This study evaluated retroperitoneal hematomas produced by bilateral injury of iliac arteries (uncontrolled hemorrhage), blood volume loss, transcapillary refill, the effects of volume replacement on retroperitoneal bleeding and the hemodynamic changes with and without treatment. METHODS: Initial blood volume was determined with Tc99m-labelled red cells, and bleeding was evaluated by means of a portable scintillation camera positioned over the abdomen. Previously splenectomized mongrel dogs (16.8 ± 2.2 kg) were submitted to hemorrhage for 30 minutes and randomized into three groups: I - no treatment (n=7); II - treatment with 32 mL/kg of Lactated Ringer's for three to five minutes (n=7); and III - treatment with 4 mL/kg of 7.5% NaCl plus 6.0% dextran 70 for three to five minutes (n=7). They were studied for an additional 45 minutes. RESULTS: Volume replacement produced transitory recovery in hemodynamic variables, including mean pulmonary artery pressure, pulmonary capillary wedge pressure and cardiac index, with significant increase in dogs treated with 32 mL/kg of Lactated Ringer's and 7.5% NaCl plus 6.0% dextran 70 (p